An investigation into the integrated pest management of the obscure mealybug, Pseudococcus viburni (Signoret) (Hemiptera: Pseudococcidae), in pome fruit orchards in the Western Cape Province, South Africa - Mudavanhu, Pride (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2009.